A pilot RCT of virtual reality job interview training in transition-age youth on the autism spectrum. (November 2021) - Genova, Helen M.; Lancaster, Katie; Morecraft, James; Haas, Mikayla; Edwards, Alexandra; DiBenedetto, Michael; Krch, Denise; DeLuca, John; Smith, Matthew J.
Highlights: Job Interviews may represent a challenge for transition age youth on the autism spectrum. The current pilot study shows preliminary feasibility and effectiveness of a virtual reality job interview training tool. Certain interview skills improved indicated by medium to large effect sizes (considered due to small sample size). Answering questions about personal strengths did not improve, likely due to limitations of the training tool. This study was implemented in a high school setting, thus VR-JIT may be a valuable tool for transition based curriculum. Abstract: Background: Adolescents on the autism spectrum may have difficulty obtaining and maintaining employment. One particular obstacle for adolescents on the autism spectrum is the job interview. The purpose of the current pilot randomized controlled trial is to examine the preliminary effectiveness and feasibility of a virtual reality job interview tool (VR-JIT) in improving job interview performance in adolescents on the autism spectrum. Method: The study was implemented in a high school setting. Fourteen adolescents on the autism spectrum were randomly divided into two groups: an experimental group (n = 7) and a services as usual (SAU) control group (n = 7). The intervention group received 10 h of VR-JIT, which includes interviewing with a virtual human and receiving feedback. All participants performed a video-recorded mock job interview at pre-test and post-test, which was rated by blinded assessors to track interview skills. Students filled out questionnaires related to job interviewing anxiety and self-efficacy pre- and post- intervention. Feasibility metrics were recorded as well. Results: Repeated Measures ANOVA revealed improved a metric of job interview performance in the experimental group following the intervention compared to the control group, indicated by medium to large effect sizes. However, perceptions of anxiety and self-efficacy did not improve following the intervention. Students reported that the intervention was easy to use and enjoyable. Conclusions: The current pilot study indicates preliminary evidence of the VR-JIT's effectiveness in improving measures of job interview performance in adolescents on the autism spectrum, even though their own perceptions did not improve. Importantly, the VR-JIT intervention was implemented in a school setting, demonstrating feasibility in its adoption as part of curriculum to help improve employment outcomes in transition age youth on the autism spectrum.